If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(b + 2) + 2(x + -5) = 2 Reorder the terms: 3(2 + b) + 2(x + -5) = 2 (2 * 3 + b * 3) + 2(x + -5) = 2 (6 + 3b) + 2(x + -5) = 2 Reorder the terms: 6 + 3b + 2(-5 + x) = 2 6 + 3b + (-5 * 2 + x * 2) = 2 6 + 3b + (-10 + 2x) = 2 Reorder the terms: 6 + -10 + 3b + 2x = 2 Combine like terms: 6 + -10 = -4 -4 + 3b + 2x = 2 Solving -4 + 3b + 2x = 2 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 3b + 4 + 2x = 2 + 4 Reorder the terms: -4 + 4 + 3b + 2x = 2 + 4 Combine like terms: -4 + 4 = 0 0 + 3b + 2x = 2 + 4 3b + 2x = 2 + 4 Combine like terms: 2 + 4 = 6 3b + 2x = 6 Add '-2x' to each side of the equation. 3b + 2x + -2x = 6 + -2x Combine like terms: 2x + -2x = 0 3b + 0 = 6 + -2x 3b = 6 + -2x Divide each side by '3'. b = 2 + -0.6666666667x Simplifying b = 2 + -0.6666666667x
| (2-z)(5z+3)=0 | | 5m+3=6m+7 | | 3(x+8)-8x=29 | | 3x^2=-6x-2 | | 9p+8q=100 | | 36x-4x+9+25x+7= | | (3x^2-6)=0 | | -(6(5xy+y^3)+5(9xy+7y^3))= | | -2a-11=7+7a | | 5x+5=-21-7x | | -3x^2-4x-5=0 | | 12p+6q=114 | | 2x*2x*2x+3x*3x*3x= | | 6a+2b=20 | | 160x-.8x^2=0 | | 200.00m+(-5600.00)=-2800.00 | | -5(x+5)=-15 | | 6p+4q=56 | | 3+2x=2(2+2x) | | 6x+-9=33 | | 200.00m+(-5600.00)=0.00 | | 3x-2(x+4)=15 | | -1.25+0.15m=0 | | (4,-4)=-5/8 | | (11w+13)+(4w-28)=180 | | 3x+7t=5 | | 3p+4q=44 | | 2x+40=16+5x | | 7-8x=202-43x | | 9x-3=-1 | | 5+2x=3x | | 2(z-3)-x=-1 |